PERSEPSI DAN STRATEGI PENGEMBANGAN WISATA PANTAI HARAPAN AMMANI DESA MATTIRO TASI KECAMATAN MATTIRO SOMPE KABUPATEN PINRANG - Widya Angriani; Muhammad Kasnir; Danial Danial (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2021)
Ammani Hamlet is located in Mattiro Tasi Village, Mattiro Sompe District, Pinrang Regency, South Sulawesi. In this area there is tourism potential, namely Harapan Ammani Beach. The purpose of this study was to determine the perception and strategy of tourism development so that Ammani Beach can be developed sustainably. This research was conducted with a qualitative descriptive method. The study was conducted for two months. The results showed that the potential for the development of Harapan Ammani beach for beach tourism was very suitable (S1) to be developed into beach tourism based on the tourism suitability index (IKW) which was 92.86%. The community's perception of the development of Harapan Ammani beach tourism is agreeing with a percentage of 100% and this indicates that Harapan Ammani beach tourism is feasible to be developed. The strategy for developing tourist objects and attraction data in the application must really pay attention to the maximum existing potential as well as facilities and infrastructure in order to create maximum attraction, so that many people want to visit.